Biology of the Downy Mildew Pathogen of Corn in Malaysia - I.B. Ahmad; D.O. Lopez; A.M. Mahir (Agriculture and Natural Resources, 1994)
The fungus isolated from corn plants exhibiting downy mildews in the field nicited similar symptoms on inoculated corn plants. Infected plants became chlorotic 2-7 days after inoculation. The biology of the aetiological fungus was study in term of the development, morphology and cytolgy of asexual fruiting structure. Conidiophores of the fungus emerge singly or in groups from stomata of infected leaves as knob-like structures after 3 hrs of incubation. The knob-likd structures measured 5.5-14.5 um in diameter and later elongted, enlarged and bifurcated to from the primary, secondary and tertiary branches. When matured, the erect conidiophores measured 180-300 um. Conidial initials start to develop at the tip or the conidiophores after 5.5 hrs, and the number of conidia per conidiophore range from 8-96. The conidia were hyaline and sub-orbicular to almost spherical in shape measuring 15-28.9 x 15-26.9 um. Most of the matured conidia are detached of discharged from the conodiophores after 7-8 hrs of incubation. The conodiophores and the conidia are multimucleated with number of nuclei ranging from one to several. Based on the above description, the fungus causing downy mildew of corn in Malaysia is tentatively identified as Peronosclerospora sorghi.